1989
DOI: 10.1037/0882-7974.4.2.251
|View full text |Cite
|
Sign up to set email alerts
|

Residual effects of cigarette smoking on cognitive performance in normal aging.

Abstract: The present study examined the residual effects of smoking status on cognitive function in 76 nondemented older adults. Current smokers, ex-smokers, and nonsmokers who were screened for health and intellectual impairments were administered a battery of standardized neuropsychological tests to measure problem solving, psychomotor speed, memory, attention span, perception, and language production. Performance decrements were found for smokers on measures of psychomotor speed. No between-group differences were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 21 publications
(24 reference statements)
1
31
0
1
Order By: Relevance
“…Table 1 shows the fact that heavysmokers who generally have a long history of smoking were the worse in TP3 performance. Our findings seems to coincident with the study by Ernst et al (2001) which showed smoking effects on visual attention (2 letter search task) and working memory but not on verbal information processing (logical reasoning task), and Hill (1989) who reported that residual effects of smoking showed on a psychomotor speed task but not on memory, attention span, perception. Ghatan et al (1998) suggested that brain activity in areas pertaining to the anterior attention system is activated by nicotine infusion.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Table 1 shows the fact that heavysmokers who generally have a long history of smoking were the worse in TP3 performance. Our findings seems to coincident with the study by Ernst et al (2001) which showed smoking effects on visual attention (2 letter search task) and working memory but not on verbal information processing (logical reasoning task), and Hill (1989) who reported that residual effects of smoking showed on a psychomotor speed task but not on memory, attention span, perception. Ghatan et al (1998) suggested that brain activity in areas pertaining to the anterior attention system is activated by nicotine infusion.…”
Section: Discussionsupporting
confidence: 71%
“…Edelstein, Kritz-Silverstein, and Barrett-Connor (1998) examined the effects of smoking on long-term memory and visual production tests and also concluded that the results offer no compelling evidence that cigarette smoking causes or prevents impaired cognitive function in old age. Hill (1989) reported that residual effects of smoking on problem solving, psychomotor speed, memory, attention span, perception and language production and showed no difference between non-smokers and ex-smokers on any measures, though smokers showed decrements only on psychomotor speed.…”
mentioning
confidence: 99%
“…On the other hand, chronic cigarette smoking is associated with cognitive impairment in several epidemiological studies (Cervilla et al, 2000). Smokers perform more poorly than both neversmokers and ex-smokers on tests of general cognitive function (Galanis et al, 2000), working memory (Ernst et al, 2001;Jacobsen et al, 2005), psychomotor speed (Hill, 1989;Kalmijn et al, 2002), cognitive flexibility (Kalmijn et al, 2002), and verbal memory and visual search (Richards et al, 2003). Berkman (Berkman et al, 1993) reported that among adults age 70-79 years, those classified as "high functioning" smoked fewer cigarettes.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding implications of dangerous behaviors in impairment, behaviors such as chronic smoking and drinking showed no significant effect on cognitive impairment in this study, debate still exists about the roles that smoking and alcohol consumption play in general cognition and incapacity (Hill, 1989;Reitz, Luchsinger, Tang, & Mayeux, 2005;Kalmijn, van Boxtel, verschuren, Jolles, & Launer, 2002).…”
Section: Discussionmentioning
confidence: 95%